ANALYSIS OF PREDISPOSING FACTORS WITH SMOKING BEHAVIOR IN ADOLESCENTS - Devi Yuliana (STIKes Ibnu Sina Ajibarang, 2023)
Background: There are various reasons behind smoking behavior in adolescents. The biggest factor of smoking habits in adolescents is social or environmental factors. Related to these factors, that a person's character is mostly formed by the surrounding environment, whether family, neighbors, or social friends (Fikriyah and Febrijanto, 2012). According to Brigham (1991) in (Tristanti, 2016), smoking is a symbolic behavior for adolescents who think that by smoking they will look more mature, mature, strong, can become leaders and can attract the opposite sex. In addition, smoking can also be a medium of relaxation, can relieve tension, make it easier to concentrate and have a pleasant experience. In theory there are other factors that make teenagers continue to smoke, namely the presence of nicotine in cigarettes, they will feel the beneficial effects of nicotine, namely for relaxation or calm, and reduce anxiety or tension. So they feel relaxed after smoking. Some teenagers who smoke report that smoking improves concentration (Fikriyah and Febrijanto, 2012). Changes from adolescents and external support must be increased to achieve a degree of health. Therefore researchers are interested in conducting research